Robustness of automated hippocampal volumetry across magnetic resonance field strengths and repeat images - Wolz, Robin; Schwarz, Adam J.; Yu, Peng; Cole, Patricia E.; Rueckert, Daniel; Jack, Clifford R.; Raunig, David; Hill, Derek (Alzheimers & Dementia, 2014)
Background Low HCV has recently been qualified by the European Medicines Agency as a biomarker for enrichment of clinical trials in predementia stages of Alzheimer's disease. For automated methods to meet the necessary regulatory requirements, it is essential they be standardized and their performance be well characterized. Methods The within-image and between-field strength reproducibility of automated hippocampal volumetry using the Learning Embeddings for Atlas Propagation (or LEAP) algorithm was assessed on 153 Alzheimer's Disease Neuroimaging Initiative subjects. Results Tests/retests at 1.5 T and 3 T, and a comparison between 1.5 T and 3 T, yielded average unsigned variabilities in HCVs of 1.51%, 1.52%, and 2.68%. A small bias between field strengths (mean signed difference, 1.17%; standard deviation, 3.07%) was observed. Conclusions The measured reproducibility characteristics confirm the suitability of using automated magnetic resonance imaging analyses to assess HCVs quantitatively and to represent a fundamental characterization that is critical to meet the regulatory requirements for using hippocampal volumetry in clinical trials and health care. © 2014 The Alzheimer's Association. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Alzheimer's disease; Clinical trials; Hippocampus; Reproducibility; Segmentation; Test/retest